The Effect of Black Pepper (Piper nigrum L.) Extract on Morphology and number of Mice (Mus musculus L.) Spermatozoa Induced by Progestin Hormone - Indriyani; Sutyarso; Busman, Hendri; Nurcahyani, Nuning; Setyaningrum, Endah (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2024)
The progestin hormone is used as male hormonal contraception. Giving progestin to normal men can  suppress libido and testicular function effectively, and reduce testosterone levels so that it can interferer with the spermatogenesis process. This study is about the effectiveness of black pepper (Piper nigrum L.) extract on morphology and number of spermatozoa in mice (Mus musculus L.)  induced by progestin. This study used a completely randomized design (CRD) which has divided into four treatment groups, each group contained 5 mice and treated according to the experimental design. Group P0 as a control (given H2O), P1 (induced by 1,25 mg progestin), P2 (induced by 1,25 mg progestin and 3.33mg/Kg BW ethanol extract of black pepper), and P3 (induced by 1,25 mg progestin and 3.33mg/Kg BW distilled water extract of black pepper). The Progestin hormone is given twice (week 1 and week 2). Black pepper extract was given daily for 35 days. Data were analyzed by one-way ANOVA and continued with the LSD test with a level of 5%. The result showed that giving of ethanol extract and distilled water extract from black pepper could improve the normal morphology and number of spermatozoa in mice after induced by progestin hormone so that fertility in men increases.